Feasibility of short imaging protocols for [18F]PI‐2620 tau‐PET in progressive supranuclear palsy. (31st December 2021) - Song, Mengmeng; Scheifele, Maximilian; Barthel, Henryk; van Eimeren, Thilo; Beyer, Leonie; Marek, Ken; Eckenweber, Florian; Palleis, Carla; Finze, Anika; Kaiser, Lena; Kern, Maike; Nitschmann, Alexander; et al.
Abstract: Background: Dynamic 60‐minute positron‐emission‐tomography (PET) imaging with the novel tau radiotracer [ 18 F]PI‐2620 facilitated accurate discrimination between patients with progressive supranuclear palsy (PSP) and healthy controls (HCs). We now aimed to investigate if shorter acquisition and static time windows of [ 18 F]PI‐2620 tau‐PET can be used for imaging of patients with PSP. Method: We evaluated 37 patients at five different centers with probable or possible PSP Richardson syndrome (PSP‐RS) together with ten HCs. [ 18 F]PI‐2620 PET was performed by a dynamic 60 minute scan. Distribution volume ratios (DVRs, multilinear reference tissue model 2, cerebellar reference) were calculated using full and truncated scan durations (0‐60, 0‐50, 0‐40, 0‐30, and 0‐20 minutes p.i.). Standardized uptake value ratios (SUVrs, cerebellar reference) were obtained from static imaging windows with 20 minutes duration (20‐40, 30‐50, and 40‐60 minutes p.i.). All DVR and SUVr data were compared with regard to their potential to discriminate patients with PSP‐RS from HCs in predefined subcortical and cortical target regions (effect size, receiver operating area under the curve (AUC), multi‐region classifier). Finally, we tested if shorter [ 18 F]PI‐2620 PET imaging can also be applied to patients with Alzheimer's disease (n=11). Result: The effect size of 0‐50 and 0‐40 DVR was equivalent to 0‐60 DVR (averaged Cohen's d: 1.22 and 1.16 vs. 1.26), whereas the performance dropped for 0‐30 or 0‐20 DVR. The 20‐40 SUVr indicated the best performance of all short static acquisition windows (averaged Cohen's d: 0.99). The globus pallidus internus discriminated patients with PSP and healthy controls at a similarly high level for 0‐60 DVR (AUC: 0.96), 0‐40 DVR (AUC: 0.96), and 20‐40 SUVr (AUC: 0.94). The multi‐region classifier sensitivity of these time windows was consistently 86%. 0‐40 DVR showed similar performance in Alzheimer's disease when compared to 0‐60 DVR. Conclusion: Short dynamic acquisition and static imaging windows can be used for [ 18 F]PI‐2620 PET imaging of PSP. 0‐40 minute dynamic scanning offers the best balance between accuracy and economic scanning and is may also be suitable for [ 18 F]PI‐2620 PET imaging of Alzheimer's disease.